2022
DOI: 10.1111/fme.12598
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a single stock of giant tiger prawns Penaeus monodon in demarcated prawn fishing zones of Tanzania

Abstract: Tanzania demarcated three prawn fishing zones along its coast to spread fishing pressure and help the prawn fishery to recover. However, it is unknown whether the demarcated zones correspond to the genetic stock structure of the world's most commercially important prawn, the giant tiger prawn (Penaeus monodon). Thus, this study used partial mitochondrial control region sequences (534 base pairs) to test the hypotheses that (1) giant tiger prawns in Tanzania's demarcated prawn fishing zones are a single stock a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Furthermore, the lack of significant genetic differentiation and geographical clustering among the sampled haplotypes reinforces the notion of extensive genetic connectivity among Barred mudskipper populations, extending beyond national borders within the SWIO, despite the reported mangrove losses. These findings are comparable to those reported in other marine species from the region, such as mangrove snails Littoraria pallescens (Nehemia et al., 2019), fiddler crabs Uca annulipes (Silva et al., 2010) and giant tiger prawns Penaeus monodon (Rumisha & Kochzius, 2023). This connectivity might be attributed to various factors, including the extended larval duration of Barred mudskipper and the influence of regional oceanic currents.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the lack of significant genetic differentiation and geographical clustering among the sampled haplotypes reinforces the notion of extensive genetic connectivity among Barred mudskipper populations, extending beyond national borders within the SWIO, despite the reported mangrove losses. These findings are comparable to those reported in other marine species from the region, such as mangrove snails Littoraria pallescens (Nehemia et al., 2019), fiddler crabs Uca annulipes (Silva et al., 2010) and giant tiger prawns Penaeus monodon (Rumisha & Kochzius, 2023). This connectivity might be attributed to various factors, including the extended larval duration of Barred mudskipper and the influence of regional oceanic currents.…”
Section: Discussionsupporting
confidence: 87%
“…However, the Kidatu population had low haplotype and nucleotide diversities, possibly due to restricted genetic connectivity with other populations in the RRB or small effective population size. Nevertheless, the relatively stable effective population size in Kidatu over time suggested that low genetic diversity may have resulted from restricted genetic connectivity that reduced genetic exchange, increased genetic drift, and reduced genetic diversity like other isolated populations (Arantes et al, 2019;Baird & Hogan, 2023;Pavlova et al, 2017;Rumisha & Kochzius, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…However, the Kidatu population had low haplotype and nucleotide diversities, possibly due to restricted genetic connectivity with other populations in the RRB or small effective population size. Nevertheless, the relatively stable effective population size in Kidatu over time suggested that low genetic diversity may have resulted from restricted genetic connectivity that reduced genetic exchange, increased genetic drift, and reduced genetic diversity like other isolated populations (Arantes et al., 2019; Baird & Hogan, 2023; Pavlova et al., 2017; Rumisha & Kochzius, 2023). Additionally, most fish caught in Kidatu were smaller in size and lower in body condition than other populations in our study, which did not conclusively indicate overfishing, but justifies further studies of population dynamics, fishing pressure, and recruitment to understand factors affecting size structure.…”
Section: Discussionmentioning
confidence: 99%
“…In Asia, combating IUU fishing significantly weakens the rising national income (Hosch and Macfadyen 2022). In addition, the molecular method is now widely used for population stock assessment of several organisms that depend on wild catches, such as blue swimming crabs and several types of shrimp (Khamnamtong et al 2021;Madduppa et al 2021;Hardianto et al 2022;Li et al 2022;Rumisha and Kochzius 2022). Adding genetic methods to fishing management activities will help the government carry out better fisheries management.…”
Section: Discussionmentioning
confidence: 99%